Detection of multiple elements in coal samples from Bangladesh by laser-induced breakdown spectroscopy - Haider, A F M Yusuf; Rony, M.A.; Lubna, R.S.; Abedin, K.M. (© 2011 Elsevier Ltd., 2017)
This article was published in the Journal Optics and Laser Technology [© 2011 Elsevier Ltd.] and the definite version is available at: 10.1016/j.optlastec.2011.04.009